RT-PCR detection of Potato leaf roll virus (PLRV) in aphids from Northern and North-Eastern India - Raigond, Baswaraj; Venkateswarlu, Vallepu; Sridhar, J; Jeevalatha, A; Sharma, Sanjeev; Singh, B P (Indian Journal of Plant Protection, 2020)
A reverse transcription polymerase chain reaction (RT-PCR) assay was developed to detect Potato leaf roll virus (PLRV) in aphids collected from potato fields. Total RNA was isolated from aphids and cDNA was synthesized with the help of random primers. In-house optimized PCR protocol for detection of PLRV targeting coat protein (CP) gene was adopted. Primers targeting cytochrome oxidase I (COI) were designed and PCR conditions were optimized so as to match with detection protocol of PLRV. However, before adopting the above optimized technique for routine detection of PLRV in aphids, the respective PCR amplified genes of PLRV (CP) and aphid (COI) were gel eluted and sequenced directly. The BLAST results revealed that both the queries showed a homology of 99 per cent each with PLRV and Myzus persicae. By adopting the developed RT-PCR technique, PLRV was successfully detected in the aphid samples collected from Shillong (Meghalaya) and Jalandhar (Punjab). Hence, this optimized technique was used to screen the aphids collected from different geographical locations for their viruliferousness with respect to PLRV. However, the virus was not present in aphids from other locations.